KSU research for corn production using SDI - Lamm, F. R., author; Spurgeon, W. E., author; Rogers, D. H., author; Manges, H. L., author (Colorado State University. Libraries, 1997)
Studies were initiated in 1989 at Kansas State University (KSU) to develop the methodology for successful application of subsurface drip irrigation (SDI) for corn production on the deep silt loam soils of western Kansas. Research efforts included evaluations of: the water requirement of subsurface drip-irrigated corn; the effect of SDI application frequency; irrigation uniformity for various length driplines; optimum dripline spacing and nitrogen management for subsurface drip-irrigated corn. SDI for row crops in the Central Great Plains is an emerging, but sound technology. Changing economic and environmental factors and/or resource constraints could result in increased adoption of this technology.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 4, 1997 at the Colby Community Building in Colby, Kansas.